Diffuse lung disease in children: Summary of a scientific conference. Issue 4 (24th June 2013) - Hamvas, Aaron; Deterding, Robin; Balch, William E.; Schwartz, David A.; Albertine, Kurt H.; Whitsett, Jeffrey A.; Cardoso, Wellington V.; Kotton, Darrell N.; Kourembanas, Stella; Hagood, James S.
Summary A multi‐disciplinary scientific conference focused on diffuse and interstitial lung diseases in children was held in La Jolla, CA in June 2012. The conference brought together clinicians (including Pediatric and Adult Pulmonologists, Neonatologists, Pathologists, and Radiologists), clinical researchers, basic scientists, government agency representatives, patient advocates, as well as children affected by diffuse lung disease (DLD) and their families, to review recent scientific developments and emerging concepts in the pathophysiology of childhood DLD. Invited speakers discussed translational approaches, including genetics and proteomics, epigenetics and epigenomics, models of DLD, including animal models and induced pluripotent stem cells, and regenerative medicine approaches. The presentations of the invited speakers are summarized here. Pediatr Pulmonol. 2014; 49:400–409. © 2013 Wiley Periodicals, Inc.